Comparison of lactated Ringer's solution and 0.9% saline in the treatment of rhabdomyolysis induced by doxylamine intoxication. Issue 4 (23rd March 2007) - Cho, Young Soon; Lim, Hoon; Kim, Seung Ho
Abstract : Objective: To compare the effectiveness and side effects of lactated Ringer's solution (LR) and 0.9% saline (NS) in the treatment of rhabdomyolysis induced by doxylamine intoxication. Methods: In this 15-month-long prospective randomised single-blind study, after excluding 8 patients among 97 doxylamine-intoxicated patients, 28 (31%) patients were found to have developed rhabdomyolysis and were randomly allocated to NS group (n = 15) or LR group (n = 13). Results: After 12 h of aggressive hydration (400 ml/h), urine/serum pH was found to be significantly higher in the LR group, and serum Na + /Cl − levels to be significantly higher in the NS group. There were no significant differences in serum K + level and in the time taken for creatine kinase normalisation. The amount of sodium bicarbonate administered and the frequency administration of diuretics was significantly higher in the NS group. Unlike the NS group, the LR group needed little supplemental sodium bicarbonate and did not develop metabolic acidosis. Conclusion: LR is more useful than NS in the treatment of rhabdomyolysis induced by doxylamine intoxication.